Black-owned small-scale building enterprises in the South African construction industry: attributes, constraints to growth and factors of success - Cattell, K S (Department of Construction Economics and Management, 2020)
The construction sector of the South African economy consists of a variety of types of enterprises. These enterprises engage in 'formal' and 'informal' construction and building activities. The distinction between these types of activities is that the latter are not recorded in official returns (Krafchik, 1990:5). Within both the formal and informal groups large-scale enterprises (LSEs), medium-scale enterprises (MSEs) and smallscale enterprises (SSEs) are found. These enterprises are owned by individuals from various race groups.